2013
DOI: 10.1038/gene.2013.64
|View full text |Cite
|
Sign up to set email alerts
|

Follicular lymphoma-protective HLA class II variants correlate with increased HLA-DQB1 protein expression

Abstract: Multiple follicular lymphoma (FL) susceptibility single-nucleotide polymorphisms in the human leukocyte antigen (HLA) class I and II regions have been identified, including rs6457327, rs3117222, rs2647012, rs10484561, rs9268853 and rs2621416. Here we validated previous expression quantitative trait loci results with real-time reverse transcription quantitative PCR and investigated protein expression in B-lymphoblastoid cell lines and primary dendritic cells using flow cytometry, cell-based enzyme-linked immuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…In silico cis -eQTL analysis of rs2647012 suggests potential regulatory function of nearby HLA class II molecules. rs2647012-T is linked to higher expression of HLA-DQB1 , an observation also reported by Sille and colleagues 20 . rs2647012-T is linked with lower expression of HLA-DQA2 , contradicting the protective effect rendered by rs2647012-T. Our results could be important as increased HLA-DQB1 expression may enhance antigen presentation, immune surveillance and the elimination of tumor cells.…”
Section: Discussionsupporting
confidence: 73%
“…In silico cis -eQTL analysis of rs2647012 suggests potential regulatory function of nearby HLA class II molecules. rs2647012-T is linked to higher expression of HLA-DQB1 , an observation also reported by Sille and colleagues 20 . rs2647012-T is linked with lower expression of HLA-DQA2 , contradicting the protective effect rendered by rs2647012-T. Our results could be important as increased HLA-DQB1 expression may enhance antigen presentation, immune surveillance and the elimination of tumor cells.…”
Section: Discussionsupporting
confidence: 73%
“…HLA class I genes including HLA-A, HLA-B , and HLA-C are expressed on the surface of all nucleated cells, whereas the expression of class II genes; HLA-DR, HLA-DQ , and HLA-DP is restricted to professional antigen presenting cells ( 1 , 2 ). Recent studies have reported varying expression levels of HLA alleles based on the quantitative polymerase chain reaction (qPCR) ( 3 9 ) and the mean fluorescence intensity (MFI) ( 10 , 11 ). The differential expression of HLA genes and alleles has been associated with immunologically mediated diseases, such as Crohn’s disease ( 7 ) and HIV ( 11 , 12 ), follicular lymphoma ( 9 ), lung cancer ( 13 ), ovarian cancer ( 14 , 15 ), and the outcome of HSCT through the increased risk of graft versus host disease (GvHD) ( 5 , 10 , 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…[1,2] Recently a few studies reported varying expression levels of HLA alleles based on the real-time polymerase chain reaction (PCR) and the mean fluorescence intensity (MFI). [310] The differential expression of HLA alleles has been associated with immunologically mediated diseases, such as Crohn’s disease [11] and HIV [6,12], follicular lymphoma[7], and the outcome of HSCT through the risk of graft versus host disease (GvHD)[8,9]. In fact, incompatibilities between the donor and the recipient in HSCT have made the expression differences of HLA molecules an interesting target for finding permissive mismatches.…”
Section: Introductionmentioning
confidence: 99%